The Turín mining prospect, Tilarán Range: a gold-bearing zone with a mineralization age of 2.0 Ma - Arauz, Alejandro (2025)
To the east of the town of Turin (Tilaran range), there is a gold mineralization consisting of a series of quartz/adularia veins, stockwork zones, and hydrothermal alteration (propylitic, argillic, and phyllic) which outcrop along the Cañita creek valley and in several old underground workings. An adularia concentrate was dated by K-Ar providing an age of 2.0 ± 0.1 Ma, corresponding to the most recent date of gold mineralization of economic interest at the national level, just in correspondence with the beginning of the Monteverde Formation volcanism, metallogenetically barren.